Regional differences and dynamic evolution of urban land green use efficiency within the Yangtze river economic belt, China - Cui, Xinghua; Lin, Mingyu; Qiu, Ying (Frontiers in Environmental Science, 2023)
In this study, we calculate the urban land green use efficiency (ULGUE) in the Yangtze River Economic Belt from 2005 to 2019 by using the epsilon-based measure (EBM) model. Further, the spatial-temporal distribution, regional differences and evolution trends of ULGUE in the Yangtze River Economic Belt are investigated in depth by using the Dagum Gini coefficient, Kernel Density estimation and Markov Chain method. The following results are obtained. 1) From the perspective of spatial-temporal evolution, the ULGUE in the Yangtze River Economic Belt show a fluctuating upward trend from 2005 to 2019, and it is manifested as diffusion from downstream to middle and upper reaches. 2) From the perspective of regional differences, there is a relatively obvious imbalance of ULGUE within the Yangtze River Economic Belt, but the differences narrow over time. 3) Considering the distribution dynamic evolution, the box diagram and distribution curve of ULGUE in the Yangtze River Economic Belt have a tendency to move to high values, but there is a more obvious phenomenon of spatial polarization. 4) For the part of time and space transfer, the ULGUE within the Yangtze River Economic Belt show the characteristic of “club convergence”, and the Spatial Markov Chain results show an obvious “spatial spillover” effect.